Dental students' perceived and actual knowledge of elder abuse: An online training curriculum. (22nd December 2019) - Nouer, Simonne S.; Meyer, Laura; Shen, Yan; Hare, Marion E.; Connor, Pamela D.
Abstract: Aims: Elder abuse, defined as emotional, physical, or sexual abuse, financial exploitation, or neglect, is a growing problem. Dental professionals have the unique opportunity to identify elder abuse. However, elder abuse awareness training, targeting dental students, is insufficient and research is limited. This knowledge gap prompted the research team at the University of Tennessee Health Science Center (UTHSC) to develop, implement, and evaluate an online Elder Abuse Awareness Professional Education Training (EAAPET) program, designed to educate dental and other health professionals to recognize, respond to, and report elder abuse. Methods and Results: Ninety‐six dental students, attending the UTHSC College of Dentistry during the fall semester of 2018, were enrolled. Pre‐ and post‐assessments, designed to assess changes in students' perceived and actual knowledge, were conducted. Paired sample t ‐test results indicate that the EAAPET program significantly improved students' perception of their abilities to identify, respond to, and report elder abuse. Improvement was also demonstrated within students' actual knowledge of how to appropriately interact with suspected elder abuse victims. Qualitative assessment suggested the training was well received by the students. Conclusions: Based on these findings, the authors recommend that dental schools integrate elder abuse awareness education into their curriculums.